International Context Indonesia's Counter-Terrorism Policy, 2001-2004 - Ali Muhammad (Jurnal Ilmiah Hubungan Internasional, 2012)
Terrorism is a serious security problem in Indonesia as indicated by a suicide bomb attack in Solo church and mosque in the Cirebon Police office complex (2011), JW Marriot (2009) and a series of terror attacks before. This article discusses the international context and the implications for the government's counter-terrorism policy. The extent to which international factors affect the government's counter-terrorism policy during the years 2001-2004? This period is considered important because it is a critical period in the war against terrorism. The argument is that global context "War on Terrorism" major impact on the direction of counter-terrorism policy in Indonesia. Led by United States (USA) and supported by its allies, international pressure has forced the government of Indonesia previously impressed hesitate to take crucial steps: for example, the application of anti-terrorism law, the arrest of the perpetrators of acts of terrorism and the "spiritual leader" of Al-Jama'ah Al-Islamiyah (Ajai)) and the prohibition Ajai. The U.S. and its allies are using a combination of instruments - in the form of an intensive diplomatic channels, financial support, technical assistance and anti-terrorism pledge to abolish the military embargo - to persuade the government that initially reluctant to follow perspective and American pressure. This article also argues that, although the government has received several international pressure and reject others because of domestic political considerations, international influence has strengthened the government's determination and capability of agents in combating terror network in Indonesia.Keywords : Indonesia, war on terror, international pressures, counterterrorism policy